2014
DOI: 10.4049/jimmunol.1302787
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor for the Complement C3a Anaphylatoxin (C3aR) Provides Host Protection against Listeria monocytogenes–Induced Apoptosis

Abstract: Listeria monocytogenes (LM) is a Gram-positive intracellular bacterium that is acquired through tainted food and may lead to systemic infection and possible death. Despite the importance of the innate immune system in fighting LM infection, little is known about the role of complement and its activation products, including the potent C3a anaphylatoxin. In a model of systemic LM infection, we show here that mice lacking the receptor for C3a (C3aR-/-) are significantly more sensitive to infection compared to WT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 62 publications
3
22
1
Order By: Relevance
“…This splenocyte depletion was not restricted to T cells as nearly all splenocyte subsets were affected. In line with the work of Strainic et al, this increased susceptibility to apoptosis in C3aR−/− splenocytes was associated with lower levels of the anti-apoptotic molecule Bcl-2 and higher levels of the pro-apoptotic receptor Fas (Mueller-Ortiz et al, 2014). To test whether the elevated apoptosis seen in C3aR−/− mice was responsible for the phenotype, C3aR−/− mice were treated with the apoptosis inhibitor Z-VAD before infection.…”
Section: Role Of the C3a And C5a Receptors In Listeriosissupporting
confidence: 83%
See 3 more Smart Citations
“…This splenocyte depletion was not restricted to T cells as nearly all splenocyte subsets were affected. In line with the work of Strainic et al, this increased susceptibility to apoptosis in C3aR−/− splenocytes was associated with lower levels of the anti-apoptotic molecule Bcl-2 and higher levels of the pro-apoptotic receptor Fas (Mueller-Ortiz et al, 2014). To test whether the elevated apoptosis seen in C3aR−/− mice was responsible for the phenotype, C3aR−/− mice were treated with the apoptosis inhibitor Z-VAD before infection.…”
Section: Role Of the C3a And C5a Receptors In Listeriosissupporting
confidence: 83%
“…Since C3aR and C5aR1 have been reported to promote splenocyte and T-cell survival under homeostatic conditions (Liszewski et al, 2013) and during T cell activation (Lalli et al, 2008; Strainic et al, 2008), it was reasoned that C3aR might protect against L. monocytogenes -induced splenocyte death. In accordance with this hypothesis, splenocyte apoptosis was significantly increased and total splenocyte numbers were significantly reduced in L. monocytogenes -infected C3aR−/− mice (Mueller-Ortiz et al, 2014). This splenocyte depletion was not restricted to T cells as nearly all splenocyte subsets were affected.…”
Section: Role Of the C3a And C5a Receptors In Listeriosissupporting
confidence: 57%
See 2 more Smart Citations
“…L. monocytogenes triggers the alternative pathway of complement activation, resulting in its opsonization by C3b and release of the complement anaphylatoxins C3a and C5a (18–20). Several studies have shown an important role for C3 and its cleavage polypeptides in the host response to L. monocytogenes (19–24). In contrast, little is known about the contribution of C5 and its major activation fragments C5a and C5b.…”
Section: Introductionmentioning
confidence: 99%